THE ROLE OF COMPARATIVE LITERATURE IN CULTURAL PROMOTION - Usmonova Sevara Sultonovna; Karimova Dilzodaxon Lazizovna (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Annotation: In the article, the theoretical foundations of comparative literature are briefly explained, its role in cultural promotion and the importance of in-depth study of the issues of literary communication today, which is one of the important conditions for understanding many artistic and aesthetic phenomena in the current literary process.